Cardiopulmonary resuscitation in the elderly: patients' and relatives' views. Issue 1 (February 1995) - Mead, G E; Turnbull, C J
Abstract : One hundred inpatients on an acute hospital elderly care unit and 43 of their relatives were interviewed shortly before hospital discharge. Eighty per cent of elderly patients and their relatives were aware of cardiopulmonary resuscitation (CPR). Television drama was their main source of information. Patients and relatives overestimated the effectiveness of CPR. Eighty-six per cent of patients were willing to be routinely consulted by doctors about their own CPR status, but relatives were less enthusiastic about routine consultation. Patients' and relatives' views about the appropriateness of CPR did not differ significantly. Seventeen percent of patients did not desire CPR. However, 64 per cent of patients were ultimately willing to follow their doctor's advice about the appropriateness of CPR. The conclusion reached is that mentally competent, elderly patients but not their relatives should be routinely consulted about their own desire for CPR in order to avoid resuscitating patients against their wishes. Further research is required to find out how patients would feel about resuscitation if they were terminally ill or chronically confused, and how carers would feel about resuscitating such patients.